2001
DOI: 10.1046/j.1440-1819.2001.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociomedical aspects of epileptic patients: Their employment and marital status

Abstract: We examined the employment and marital status of adult patients with epilepsy who did not have mental retardation and who had been treated at Hirosaki University Hospital, Hirosaki, Japan, for more than 5 years. The present study included 278 patients (142 males and 136 females) ranging from 20 to 60 years of age. We investigated the occupational status of the subjects and found that 168 had permanent jobs, but 41 patients were unemployed at the time of this survey. The proportion of the patients whose seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
27
1
Order By: Relevance
“…[22] Other studies have indicated that marital status in person with epilepsy has been associated with lower QOL. [8] This study showed that married adult patients with epilepsy have a better life than unmarried patients in different ages possibly due to age and marriage having interactions. By psychological counseling and clinical drug intervention measures, we hope to improve the adult epilepsy patients on the quality of life in all ages of marriage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[22] Other studies have indicated that marital status in person with epilepsy has been associated with lower QOL. [8] This study showed that married adult patients with epilepsy have a better life than unmarried patients in different ages possibly due to age and marriage having interactions. By psychological counseling and clinical drug intervention measures, we hope to improve the adult epilepsy patients on the quality of life in all ages of marriage.…”
Section: Discussionmentioning
confidence: 95%
“…[2345] It is generally agreed that people with epilepsy are less likely to marry and more likely to divorce than the general population. [678] Although epilepsy impacts various social aspects, marriage is a primary source of social support and a predictor of health status. [9] Previous studies also suggest that married persons report better psychological and physical health compared to those who are not married.…”
Section: Introductionmentioning
confidence: 99%
“…of sick leaves (Lassouw et al, 1997) Vocational training (Lassouw et al, 1997) Injury frequency during seizure attack (Dennerll et al, 1966) Others: Seizure diagnosis (Herodes et al, 2001;Sillanpaa et al, 1998;Wheless, 2006) Seizure severity (De Boer, 2005;Lim et al, 2013c) Epilepsy Type (Lim et al, 2013c;Pal et al, 2008) Age of surgery epilepsy (George et al, 2009;Zarroli et al, 2011) Having partial seizure history (Jacoby et al, 2005) Seizure epilepticus (Sillanpaa and Schmidt, 2010) Responsiveness to AED (Lim et al, 2013c) Side effect of AED (Wheless, 2006) Medicine compliance (Chen et al, 2010) Approval of LEV (Korchounov et al, 2012) History of psychotic test (Wada et al, 2001) Post ATL follow-up duration (George et al, 2009) Others: Types of antiepileptic drug (Haag et al, 2010) Use of antiepileptic drugs (Jacoby et al, 2005) History of Convulsion (Bautista and Wludyka, 2007) History of GTC in last year (Lee, 2005) Side effect of AED (Bautista and Wludyka, 2007) Side of lesion (Bautista and Wludyka, 2007;Zarroli et al, 2011) Timing of seizure attack (Elwes et al, 1991;Lee, 2005;The RESt-1 Group, 2000) Others:…”
Section: Socio-demographic Factors (N = 42 Papers)mentioning
confidence: 99%
“…10 Lower rates of marriage and greater social isolation have been reported in adults with epilepsy as compared with others. 11 Some, though not all, people with epilepsy feel stigmatised by their condition. 12 The relationship between the severity of epilepsy and its impact on QOL is complex and may be determined by a number of different factors.…”
mentioning
confidence: 99%